EMPIRICAL RESEARCH ON FINANCIAL LITERACY - N, Anusha; M, Srikanth; GK, Ramya (International Journal of Research -GRANTHAALAYAH, 2025)
Financial literacy, the ability to understand and apply financial principles effectively, plays a critical role in personal financial management, economic stability, and overall well-being. This research delves into empirical studies on financial literacy, examining its determinants, impacts, and interventions aimed at improving financial knowledge across different demographics. By synthesizing findings from various studies, this paper highlights the importance of financial literacy in fostering better financial behaviors and reducing economic disparities.